2017
DOI: 10.12659/ajcr.905089
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally High Creatine Kinase (CK) Levels in Multicausal and Complicated Rhabdomyolysis: A Case Report

Abstract: Patient: Male, 36Final Diagnosis: Rhabdomyolysis induced acute renal failureSymptoms: Diarrhea • generalized weaknessMedication: —Clinical Procedure: Hemodialysis • intubationSpecialty: Critical Care MedicineObjective:Unusual setting of medical careBackground:Rhabdomyolysis is a syndrome caused by muscle breakdown. It can be caused by traumatic as well as non-traumatic factors such as drugs, toxins, and infections. Although it has been initially associated with only traumatic causes, non-traumatic causes now a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 6 publications
1
20
0
1
Order By: Relevance
“…CK employ adenosine-triphosphate to catalyze the transformation of creatine into adenosine diphosphate and phosphocreatine. The higher the CK activity higher the tissue damage causing acute kidney injury, rhabdomyolysis, muscular dystrophy, myocardial infarction and autoimmune myositis 28,29 .…”
Section: Resultsmentioning
confidence: 99%
“…CK employ adenosine-triphosphate to catalyze the transformation of creatine into adenosine diphosphate and phosphocreatine. The higher the CK activity higher the tissue damage causing acute kidney injury, rhabdomyolysis, muscular dystrophy, myocardial infarction and autoimmune myositis 28,29 .…”
Section: Resultsmentioning
confidence: 99%
“…Since that time, at least 17 additional cases have been reported in the literature [622]. Our patient had one of the highest ever reported CK levels [23]. The exact mechanism leading to muscular injury in case of Legionella infection remains unclear.…”
Section: Discussionmentioning
confidence: 92%
“…Various case reports on IMNM describe CK levels rising to around 28,000 iU/L. In one of the largest case studies, the mean peak CK reported for each of a variety of different causes ranged from approximately 10,000 to 25,000 iU/L [ 4 ]. To our knowledge, our patient’s CK levels were one of the highest recorded, at 36,000 then 53,000 iU/L on relapse.…”
Section: Discussionmentioning
confidence: 99%